Synthesis of Closely‐Contacted Cu2O‐CoWO4 Nanosheet Composites for Cuproptosis Therapy to Tumors With Sonodynamic and Photothermal Assistance - Zhuoran Yang; Zhuo Li; Chunyu Yang; Li Meng; Wei Guo; Liqiang Jing (Advanced Science)
Abstract Cuproptosis offers a promising and selective therapeutic strategy for cancer therapy. To fully realize its potential, the development of novel cuproptosis therapeutic agents and the achievement of efficient copper release are critical steps forward. Herein, closely‐contacted Cu2O‐CoWO4 nanosheet heterojunctions (CCW‐NH) are successfully synthesized using an in‐situ process for cuproptosis therapy. The efficient release of copper ions from CCW‐NH can be triggered by ultrasound irradiation, primarily due to the generation of superoxide radicals as the sonodynamic agents via the Z‐scheme charge transfer mechanism. When subjected to the combined effects of ultrasound and laser irradiation, the effective release of copper ions is increased by 1.7 times compared to the untreated group, significantly enhancing the efficiency of cuproptosis. And the incorporation of CCW‐NH and L‐arginine into the temperature‐sensitive injectable hydrogel (HP‐CCW@LA) ultimately achieved a tumor inhibition rate of up to 95.1%. L‐arginine, serving as a reducing agent, enabled the sustained release of highly active Cu+ during treatment. Notably, after treating tumors with HP‐CCW@LA, the tumor microenvironment is leveraged to promote copper ion conversion, which offers the potential for monitoring tumor therapy efficacy through magnetic resonance imaging. This work offers a novel integrated strategy for the development of new cuproptosis agents and therapeutic evaluation.